2021
DOI: 10.1007/s00392-021-01918-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation in patients with a small aortic annulus: performance of supra-, intra- and infra-annular transcatheter heart valves

Abstract: Background A small aortic annulus is associated with increased risk of prosthesis–patient mismatch (PPM) after transcatheter aortic valve implantation (TAVI). Whether specific transcatheter heart valve (THV) designs yield superior hemodynamic performance in these small anatomies remains unclear. Methods Data from 8411 consecutive patients treated with TAVI from May 2012 to April 2019 at four German centers were retrospectively evaluated. A small aortic ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The fact that SAV implantation was the only independent predictor of severe PPM and that the multivariable predictor analysis of PPM including SAV performed better than that including SEV reinforce the concept that leaflet position in the subgroup of patients analyzed in the current study is key for forward hemodynamics after TAVI. Even though recent studies linked SEV implantation to lower incidence of PPM and better hemodynamics independently from leaflet position, 32 our results confirm previous evidence suggesting a benefit of this valve design in small aortic annuli 14,33,34 …”
Section: Discussionsupporting
confidence: 89%
“…The fact that SAV implantation was the only independent predictor of severe PPM and that the multivariable predictor analysis of PPM including SAV performed better than that including SEV reinforce the concept that leaflet position in the subgroup of patients analyzed in the current study is key for forward hemodynamics after TAVI. Even though recent studies linked SEV implantation to lower incidence of PPM and better hemodynamics independently from leaflet position, 32 our results confirm previous evidence suggesting a benefit of this valve design in small aortic annuli 14,33,34 …”
Section: Discussionsupporting
confidence: 89%
“…The gradients were in the single-digit range even in patients with a very small annulus who had been treated with the 23-mm valve. 12 , 13 This finding is very remarkable for a valve with an intra-annular design and is rather comparable to supra-annular devices from a hemodynamic point of view. 14 Apart from that, the intra-annular design is usually associated with better accessibility of the coronary ostia.…”
Section: Discussionmentioning
confidence: 78%
“…Studies have shown that SEV have better valve haemodynamics and lower PPM rates than BEV. 29,30 Anatomically, the result of better haemodynamics may be driven by the supra-annular location in SEV compared with intra-annular location in BEV. 21 These findings were also seen in our study but primarily in the SAA group.…”
Section: Discussionmentioning
confidence: 99%